(untitled) (Khairulummah, 2022)
Allah, the Almighty, is the creator of the entire world. He has meticulously maintained it since the beginning. He creates humans and provides them explicit instructions on how to live their lives. Depending on their actions, he will reward or punish them in the afterlife. He never strays from His own administrative or ruling policies, ideologies, methodologies, or strategies. Every creation of the cosmos is given specified fundamental traits or characters, and no changes or adjustments are detected in how they are sustained, how they are "Governed by Allah," or what material properties they contain, like His administrative policy. This is something that the Holy Quran encourages us to do. In the Holy Quran. And Science is the branch of knowledge that deals with the physical world. "How does our knowledge of the physical world expand?" is a question that must be answered in scientific inquiry. Every material in the cosmos has been endowed with unique fundamental qualities by the Almighty Allah. Only a few of those features can be discovered and applied in an integrated form when and where they are required. Islam created its own unique science culture and heritage at the pinnacle of its civilization’s scientific achievement. It created a culture of research and knowledge that advanced and thrived under the paradigm of divine unity and universe unity and mirrored the Islamic value system. Islam has long attempted to reconcile the sacred with the mundane. In Islam, the use of knowledge and science is for the greater good and in accordance with the Creator’s goals. As a result, education was viewed as a tool to achieving higher moral and spiritual goals rather than an end. In Islamic Science, unlike modern science, there is no dehumanization, abstraction, or alienation.